2020
DOI: 10.1590/1678-5150-pvb-6615
|View full text |Cite
|
Sign up to set email alerts
|

Testicular tumors in 190 dogs: clinical, macroscopic and histopathological aspects

Abstract: This study aimed to characterize the prevalence and clinical, macroscopic and histopathological aspects of dogs affected by testicular tumors based on biopsy specimens from the Laboratório de Patologia Veterinária of the Universidade Federal de Santa Maria (LPV-UFSM) over 19 years. Parameters regarding the age, size, and breed of the affected dogs were also established. Of all dogs with some type of neoplasm submitted to histopathological analysis at the LPV over these 19 years (n=1,900), 213 (11.2%) had at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
4
9
1
1
Order By: Relevance
“…Cryptorchidism and age are the main predisposing factors for the development of canine testicular tumors [2,6]. The mean age of dogs with testicular neoplasms is about 10 years [1,[7][8][9][10][11]. Several studies have shown breed predisposition for testicular tumors, particularly in Sheltie, Collie, Boxer, German Shepherd, Fox Terriers, Afghan Hounds, and Norwegian Elkhounds [8,9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptorchidism and age are the main predisposing factors for the development of canine testicular tumors [2,6]. The mean age of dogs with testicular neoplasms is about 10 years [1,[7][8][9][10][11]. Several studies have shown breed predisposition for testicular tumors, particularly in Sheltie, Collie, Boxer, German Shepherd, Fox Terriers, Afghan Hounds, and Norwegian Elkhounds [8,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…[3,5,[14][15][16]. The most common types of canine testicular tumors are interstitial cell tumors, seminoma, and Sertoli cell tumors; however, the incidence of these neoplasms varies among studies [7,9,10,12]. To the best of our knowledge, retrospective studies with a large sample size describing epidemiologic data on canine testicular tumors in Russia have not been published.…”
Section: Introductionmentioning
confidence: 99%
“…It is uncommon for more than one type of testicular tumor to develop in the same testicle. There have been previous reports of more than one type of testicular neoplasm occurs in 8.4% (16/190), the most common combination of tumors SEM-ICT, followed by SEM-SCT and SCT-ICT (9). Our patient had tumors in both testicles, and one testis had developed more than one type of testicular tumor.…”
Section: Discussionmentioning
confidence: 43%
“…The prevalence of testicular tumors varies from 11.2% to 27% in male dogs, with a higher incidence in the presence of cryptorchidism (1,9). Although the incidence of tumors varies among studies, SEMs and ICTs occur frequently, and SCTs and mixed germ cell-sex cord-stromal cell tumors occur less frequently (1,6,9). SCTs are the uncommon in dogs, but in dogs with cryptorchidism they are the most common tumors to develop (4).…”
Section: Discussionmentioning
confidence: 99%
“…We focused our attention on breeding dogs to evaluate the possibility of preserving their fertility. In addition, an early diagnosis of a testicular tumor can also reduce the risk of metastasis, even if that occurs less frequently in dogs than humans [ 23 ].…”
Section: Introductionmentioning
confidence: 99%